2020
DOI: 10.1038/s41598-020-71064-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activity at the AlN/Si Interface: identifying the main origin of propagation losses in GaN-on-Si devices at microwave frequencies

Abstract: AlN nucleation layers are the basement of GaN-on-Si structures grown for light-emitting diodes, high frequency telecommunication and power switching systems. In this context, our work aims to understand the origin of propagation losses in GaN-on-Si High Electron Mobility Transistors at microwaves frequencies, which are critical for efficient devices and circuits. AlN/Si structures are grown by Metalorganic Vapor Phase Epitaxy. Acceptor dopant in-diffusion (Al and Ga) into the Si substrate is studied by Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…In contrast, a fast decrease from 1824 to 869 Ω/□ can be seen for increasing TMAl predose from 6 to 12 s. As R SH = ρ channel /t, where ρ and t denote the channel resistivity and thickness, considering t of the SCM-resolved p-type layer to be ∼3 μm and approximating a uniform distribution, these values reveal an associated resistivity of ∼0.2−0.6 Ω cm, suggesting 51 10 16 −10 17 cm −3 acceptors on average for the whole layers. Notably, such magnitudes of unintentional doping agree well with both the estimated volume concentration of holes 32 in the p-type layer and the ranges of the reported 26,27,29 SIMS depth profiles for group-III species. Also, in conjunction with the Hall effectmeasured n-type carrier concentrations (i.e., mid-10 13 cm −3 ), these values of p-type carriers should result in a p−n junction depletion region of ∼4 μm, quite consistent with those observed in SCM.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…In contrast, a fast decrease from 1824 to 869 Ω/□ can be seen for increasing TMAl predose from 6 to 12 s. As R SH = ρ channel /t, where ρ and t denote the channel resistivity and thickness, considering t of the SCM-resolved p-type layer to be ∼3 μm and approximating a uniform distribution, these values reveal an associated resistivity of ∼0.2−0.6 Ω cm, suggesting 51 10 16 −10 17 cm −3 acceptors on average for the whole layers. Notably, such magnitudes of unintentional doping agree well with both the estimated volume concentration of holes 32 in the p-type layer and the ranges of the reported 26,27,29 SIMS depth profiles for group-III species. Also, in conjunction with the Hall effectmeasured n-type carrier concentrations (i.e., mid-10 13 cm −3 ), these values of p-type carriers should result in a p−n junction depletion region of ∼4 μm, quite consistent with those observed in SCM.…”
Section: Introductionsupporting
confidence: 84%
“…Very recently, the presence of a p-type layer followed by a depletion region that is formed with the FZ-grown n-type substrate has been evidenced by Bah 32 et al through coupled SCM and SSRM experiments. For AlN grown with a fixed NH 3 predose, those authors had observed a proportional relationship between the AlN growth temperature and the width of the p-type layer.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…SCM measurements are performed using a Bruker Dimension Icon AFM apparatus equipped with a Nanoscope V controller. The SCM technique is a useful tool dedicated to the 2D electrical profiling of carrier concentration in semiconductor devices, especially at material interfaces [57]. SCM experimental setup includes AFM conductive probe, ultra-high frequency (~ 1 GHz) capacitance sensor, lock-in amplifiers, multi-channel signal processing systems and 2D map plotters.…”
Section: Scanning Capacitance Microscopy (Scm)mentioning
confidence: 99%